PENGARUH STRUKTUR AKTIVA, LIKUIDITAS, DAN UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN TEKSTIL DAN GARMENT - YOSAR HARITSAR (Jurnal Akademika, 2020)
This study aims to determine the structure of liquidity assets, the size of the company, profitability partially and simultaneously significant effect on the capital structure of textile and garment companies listed on the Indonesia Stock Exchange for the period 2015-2019. Sampling in this study using purposive sampling method, namely the selection of sample companies during the study period based on certain criteria in order to obtain a sample of 13 companies. The results showed that partially the effect of asset structure on capital structure in line with signal theory, liquidity did not have a significant effect on capital structure. Firm size does not have a significant effect on capital structure. The effect of profitability on capital structure is in accordance with the pecking-order theory. Simultaneous or joint testing shows that all independent variables, namely asset structure, liquidity, company size, and profitability have a significant influence on capital structure. Keywords: asset structure, liquidity, company size, profitability, capital structure.